Evaluating the Professional Practice of Pharmacists Working at Pharmacies in Isfahan City, Iran - Sayed Abolfazl Mostafavi; Mohsen Chamanara; ٍٍٍٍEhsan Khabazian (مجله دانشکده پزشکی اصفهان, 2013)
Background: Pharmacists, in community pharmacy, play an important role in public health as they serve as guardians of the accuracy of dispensed prescription. Although the assessment of professional competence for this profession is a difficult task, however, evaluation of this profession may help for giving better services and is needed for safe use of medications. The aim of this study was evaluation of dispensing accuracy and counseling provided by community pharmacists.